2018
DOI: 10.1155/2018/5678781
|View full text |Cite
|
Sign up to set email alerts
|

Association of Poor Social Support and Financial Insecurity with Psychological Distress of Chronic Kidney Disease Patients Attending National Nephrology Unit in Sri Lanka

Abstract: Background Chronic kidney disease (CKD) is associated with high morbidity and mortality. Hence, CKD patients are often in chronic psychological distress. The objective of the study was to describe factors associated with psychological distress of CKD patients attending National Nephrology Unit. Methods A descriptive cross-sectional study was conducted among 382 CKD patients above 18 years of age applying systematic sampling. The data was collected using self-administered questionnaires to assess the psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(27 reference statements)
1
3
0
2
Order By: Relevance
“…[26] przeprowadzonym na 273 dializowanych pacjentach w Chinach autorzy oszacowali częstość występowania niespecyficznych zaburzeń psychicznych na poziomie 45,8% (GHQ-28) [26]. Inne badania opisują występowanie tych zaburzeń na poziomie 55,2% do 75,0% (GHQ-12) [27,28]. W porównaniu z naszymi wynikami i z ustaloną wysoką częstotliwością występowania objawów depresyjnych i lękowych w populacjach ESRD (End-Stage Renal Disease -Schyłkowa niewydolność nerek) te liczby nie wydają się wyższe, niż oczekiwano.…”
Section: Dystres Psychologiczny I Objawy Psychopatologiczneunclassified
See 1 more Smart Citation
“…[26] przeprowadzonym na 273 dializowanych pacjentach w Chinach autorzy oszacowali częstość występowania niespecyficznych zaburzeń psychicznych na poziomie 45,8% (GHQ-28) [26]. Inne badania opisują występowanie tych zaburzeń na poziomie 55,2% do 75,0% (GHQ-12) [27,28]. W porównaniu z naszymi wynikami i z ustaloną wysoką częstotliwością występowania objawów depresyjnych i lękowych w populacjach ESRD (End-Stage Renal Disease -Schyłkowa niewydolność nerek) te liczby nie wydają się wyższe, niż oczekiwano.…”
Section: Dystres Psychologiczny I Objawy Psychopatologiczneunclassified
“…Ponadto stwierdzono istotne różnice między płcią męską i żeńską dla podskali "Pobudzenie" (IES-R), gdzie mężczyźni uzyskali istotnie niższy wynik niż kobiety. Wynik ten jest zgodny z innymi badaniami dotyczącymi zdrowia psychicznego podczas pandemii SARS-CoV-2, gdzie dystres psychologiczny występował częściej u kobiet, lecz również z publikacjami dotyczącymi pacjentów z przewlekłą chorobą nerek, niezależnie od pandemii [27,35,36]. Hettiarachchi i Abeysena [27] ustalili, że pacjentki płci żeńskiej z PChN wykazywały wyższy wskaźnik dystresu psychologicznego (mierzonego za pomocą GHQ), co potwierdził w swoim badaniu również Sfyrkou [36], opisując wyższy wynik dystresu psychologicznego u kobiet z ESRD (mierzonego z użyciem Kessler Psychological Distress Scale-K10).…”
Section: Objawy Ptsdunclassified
“…Income is one of the key determinants related to CKD. According to Hettiarachchi and Abeysena (2018) and Weerasekara (2017) have revealed that the majority of kidney patients do not earn an adequate income. Some of the important clinical factors identified concerning CKD under empirical studies are the time of having diabetes, time of having high blood pressure, duration of using Ayurveda medicines, family history of kidney failure, and also Body Mass Index (BMI).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 12-item General Health Questionnaire (GHQ-12) The Chinese version of the 12-item General Health Questionnaire (GHQ-12) was used to detect the level of general mental health among haemodialysis patients. This instrument was developed by Goldberg and revised by scholar Taian Cheng (Goldberg David & Williams, 1988;Cheng & Williams, 1986). The common method is binary GHQ scoring (0-0-1-1), which yields a possible score range of 0-12.…”
Section: Instrumentsmentioning
confidence: 99%